The time course of the inflammatory response to the Salmonella typhi vaccination - Paine, Nicola J.; Ring, Christopher; Bosch, Jos A.; Drayson, Mark T.; Veldhuijzen van Zanten, Jet J. C. S. (Brain, behavior and immunity, 2013)
The Salmonella typhi vaccination induces transient increases in inflammatory-responsive cytokines and molecules. For instance, it causes small, mild increases in interleukin-6 (IL-6) within a few hours and C-reactive protein (CRP) within 24h. No study has charted either the time course of the inflammatory response to this vaccine or any associated changes in mood, physical symptoms, and cardiac function. In a blinded crossover experimental design, eight participants received the S. typhi vaccine (vaccination condition) and a saline (control condition) injection on two separate days, at least one week apart. Blood samples and mood ratings were collected at 0, 4, 5, 6, 7, 8 and 24h post-injection, physical symptoms and pain were assessed at 4-8 and 24h post-injection, and cardiovascular function was recorded until 8h post-injection. Repeated measures analyses of variance and polynomial trend analyses compared the timecourse of the response patterns between the two conditions. Whereas there were no temporal changes in the control condition, the vaccination increased granulocytes, IL-6, TNF-α, and CRP (all p’s<.05). Specifically, the granulocytes, IL-6 and TNF-α peaked after 6-8h while CRP peaked after 24h. This vaccine-induced mild inflammatory response was not accompanied by any changes in mood or cardiovascular activity. We also found that participants tended to report more pain in the injected limb in the vaccination condition (p<.07). In sum, our study charted the timecourse of key inflammatory-responsive markers following S. typhi vaccination and identified the timing of their modest peaks. It is worth noting that changes in these markers were not accompanied by any notable changes in mood or cardiovascular activity, and thus the S. typhi vaccination is a suitable method to induce increases in inflammatory-responsive markers, without altering mood or cardiovascular parameters.